An Analysis of Students’ Problems in Developing Speaking Skill at Eighth Grade - Parawangsa, Khofifah Indar; Islam, Muhammad Hifdil; Ferdiyanto, Feri (International Journal of English Education and Linguistics (IJoEEL), 2024)
Speaking is a subject matter that must be learned by the students because it is the most important factor in the development of English language skills. Therefore, the aim of this research is to describe the difficulties that students face when learning English, especially when developing their speaking skills. The researchers analyze the problem and causes of speaking English for eighth grade students. The researchers had already observed the students when they learned English, especially in speaking. The descriptive methodology used in this study is qualitative. Data from interviews and direct observation were used to learn more about students' challenges as they tried to improve their English. Based on the data analyzed, the result of the research found the students problems, including the cause of problems in English speaking. In speaking English, every student has their own typical problems, but in general, those can be stated as follows: lack of vocabulary, grammar, pronunciation, comprehension, and fluency. The researchers also found that the causes of students problems are, lack of  self-confidence, afraid of making mistakes, shyness, anxiety, lack of motivation, and relying on English lessons at school.